One health approach unravels worrying antimicrobial resistance patterns: A cross-sectional study in Kisii, Kenya - Briton M. Kavulavu; Eric O. Omwenga; Oscar Asanya Nyangiri; Andrew K. Nyerere; Rael J. Too; Elizabeth J. Matey; Siri Göpel; Wycliffe Mogoa; Thorben Schilling; Ludwig E. Hoelzle; Beryl Primrose Gladstone (PLoS ONE, 2025)
Background Antimicrobial resistance (AMR) is a major public health challenge, particularly in Sub-Saharan Africa, where diagnostic and surveillance capacities are limited. Enterobacterales significantly contribute to AMR, with environmental reservoirs facilitating transmission between humans, animals, and the environment. Methods This study investigated the prevalence and antimicrobial susceptibility of selected Enterobacterales in human, water, animal feces, and soil samples in Kenya. A cross-sectional study including 200 patients with gastrointestinal symptoms was conducted at Kisii Teaching and Referral Hospital and surrounding areas. AMR testing was performed using the disk diffusion method. Results A total of 365 samples were collected: 200 human and 55 each of water, animal feces, and soil specimens from the homesteads of patients with resistant isolates. 343 isolates were obtained (Escherichia coli: 280/343 [81.6%], Salmonella spp.: 28/343 [8.2%], Klebsiella spp.: 25/343 [7.3%], Shigella spp.: 10/343 [2.9%]). A significant proportion of isolates exhibited AMR, particularly to piperacillin-tazobactam (up to 87%) and ampicillin (up to 79%). Resistance to piperacillin-tazobactam in E. coli was the highest, observed in humans (100/139, 71.9%), water (42/49, 85.7%), animal feces (9/46, 19.6%), and soil (33/46, 71.7%). Almost half (45%) of the human isolates showed ESBL production or resistance to imipenem, with water, animal feces, and soil samples, revealing similar resistance patterns. Resistance to chloramphenicol (71.7% vs 20.1%; p < 0.001) and third-generation cephalosporins were higher among animal and environmental isolates (animal feces: cefotaxime – 25/46, 54.3%; ceftazidime – 27/46, 58.7%) as compared to human isolates (cefotaxime – 40/139, 28.8%; ceftazidime – 28/139, 20.1%) (p < 0.001). In human isolates, the most prevalent genes were blaTEM (53/187, 28.3%), blaOXA-48 (43/187, 23.0%), blaSHV (32/187, 17.1%), and blaCTXM-15 (41/187, 21.9%); in animal isolates, blaCTXM-8 (11/55, 20.0%), blaVIM (8/55, 14.5%), and blaTEM (8/55, 14.5%) were most detected; while in soil and water isolates, blaCTXM-8 was the most common (10.9% and 9.1% respectively). Conclusion Shared resistance patterns across human, animal, and environmental samples highlight interconnected AMR pathways. These findings reinforce the need for a One Health approach through integrated AMR surveillance and interventions.